Perceived health, quality of life and happiness among older professional artisans in a UNESCO Creative City of crafts and folk art - Igreja, Sandra; Teles, Soraia; Paúl, Constança (Frontiers in Psychology, 2025)
Globally, it is a priority to understand how to improve health, quality of life, and happiness in a long-lived and rapidly aging population. Evidence on the health outcomes of working in later life is mixed, with some studies suggesting it benefits mental health by preserving identity, status, social participation, and a sense of purpose, while others highlight potential adverse effects. Research on aging at work has seldom focused on older adults professionally engaged in artistic activities, particularly across different craft sectors, in contrast to the extensive research on art-based interventions aimed at promoting well-being among older individuals. This study aims to describe the perceptions of health, quality of life, and happiness among older professional artisans from a UNESCO Creative City of Crafts and Folk Art in Portugal, and examine the associations with sociodemographic and professional variables. A cross-sectional study was conducted, involving primary data collection through a survey administered in the participants’ (N = 55) work environments. Eligible participants were individuals aged 55 or older, living in the community, and working in various craft sectors. The artisans completed the WHOQOL-BREF scale, were assessed for depressive symptoms with the PHQ-8 scale, and were inquired on happiness with life using an item from the European Survey on Aging Protocol (ESAP). Most artisans perceived their overall quality of life as ‘good’, with the psychological domain receiving the highest score (M = 84.92; SD = 10.98). Most artisans (56.4%) also reported feeling ‘very happy’ and being satisfied or very satisfied with their health (60%). Age was positively correlated with happiness (p = 0.020). A significant difference was observed in the WHOQOL-BREF environment domain between craft sectors (p = 0.023). An association was observed between different craft sectors and their perceived benefits, particularly regarding health, quality of life, and well-being. This study contributes to aging research by focusing on professional activity in the craft and folk art sector, highlighting the intersection of aging, work, and artistic engagement, and offering insights for policy development to support aging craftspeople and promote traditional crafts.